Isolation and Identification of Bacteria from Lung of Apparently Health Camels Slaughtered in Jigjiga Municipality Abattoir, Somali region, Ethiopia (Global Journal of Medical Research, 2017)
The study was conducted at Jijiga from October 2009 to May 2010 to isolate and identify the bacterial species from the lung of apparently healthy camels slaughtered in Jijiga Municipality Abattoir. Samples were collected aseptically from the lung for bacteriological examination. Standard microbiological techniques were used for the isolation and identification of the bacterial species. A total of 65 lung samples were examined bacteriologically and the most common lung lesions encountered were pneumonic (64.60%), emphysematous (20%) and 15.40% of necrotic foci. The bacterial species that were isolated include Coagulase negative staphylococci (48.7%), Streptococcus pneumonae (20.5%), Escherichia coli (12.8%), Rhodococcus equi (5.1%), Manhaemia hemolytica (7.7%), Corynebacterium kutcheri (2.6%) and Corynebacterium pseudotuberculosis (2.6%). Result of present study showed that Coagulase Negative Staphylacocci, Streptococcus pneumonae, Escherichia coli and Manhaemia hemolytica were the most important bacteria inhabiting the respiratory tract of camels and therefore these bacteria may cause respiratory diseases when associated with stress factors.
Keywords: camel; lung lesion; bacteria; microbiological techniques; jijiga